Legal Defect of Verstek Decision with Invalid and Proper Summons in the Context of Civil Procedure Law - Nurfaizah, Hartika; Sholehudin, Miftahus (Al-Bayyinah, 2023)
The summoning process delivered in the form of a summons to the parties involved is the initial stage of the trial which must be carried out legally and properly to ensure justice takes place. This research seeks to examine the new concept of procedural law related to the form as well as the validity and properness of a summons after the issuance of PERMA No. 7 of 2022 as well as the legal consequences of the decision of the panel of judges who have committed unprofessional conduct by deciding the verstek case Number 908/Pdt.G/2023/PA.Bkl even though the summons was not carried out valid and properly. This type of research is normative juridical using a case and legislative approach and primary legal material is taken from decisions and secondary legal material from literature and research journal articles. The results showed that cases filed electronically were summoned by registered letter through the intermediary of a courier service provider that could not only be received by the party concerned but could also be received by adults living in the same house, receptionists, and local security officers. If the registered letter is returned to the court with a statement that the address is not found, the next mechanism is carried out through a public summons. Therefore, Decision Number 908/Pdt.G/ 2023/PA.Bkl which was rendered by verstek is null and void due to a legal defect in the summoning process which was not carried out in accordance with number 10 of SEMA Number 1 of 2023 and does not meet the requirements to be declared verstek. All rights of the defendant must be protected through a carefully issued decision because not all parties can understand the legal process, especially since this decision will only be canceled if it is submitted for annulment by the defendant because this case is in the civil realm.